2015
DOI: 10.1016/j.recot.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Alta recidiva y buenos resultados funcionales tras la resección artroscópica de la sinovitis villonodular pigmentaria de la rodilla

Abstract: Pigmented villonodular synovitis treated by arthroscopic resection showed good functional results at mid-term follow-up. A single arthroscopic resection was sufficient to treat the localised PVS, whereas the diffuse type of PVS required a second arthroscopic resection in most cases, due to its high rate of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The recurrence rate of the PVNS is as high as 10–50% for the residual diseased synovium after the simple synovectomy [ 21 ]. Isart A et al [ 22 ] also reported a high recurrence of PVNS (61.5%, 8/13) after arthroscopic synovectomy. Moreover, it is almost impossible to resect the pathological synovium completely by open access or arthroscopic therapy [ 23 ].…”
Section: Discussionmentioning
confidence: 98%
“…The recurrence rate of the PVNS is as high as 10–50% for the residual diseased synovium after the simple synovectomy [ 21 ]. Isart A et al [ 22 ] also reported a high recurrence of PVNS (61.5%, 8/13) after arthroscopic synovectomy. Moreover, it is almost impossible to resect the pathological synovium completely by open access or arthroscopic therapy [ 23 ].…”
Section: Discussionmentioning
confidence: 98%